23 Impact of COVID-19 in gynecologic oncology: a nationwide Italian survey. (13th November 2020) - Bogani, G; Apolone, G; Ditto, A; Scambia, G; Benedetti Panici, P; Angioli, R; Pignata, S; Greggi, S; Scollo, P; Mezzanzanica, D; Franchi, M; Di Donato, V; et al.
Abstract : Objective: Several attempts are done in order to control COVID-19 and promote a fair allocation of resources during the outbreak. The Italian society of obstetrics and gynecologist (SIGO), and the Multicenter Italian Trials in Ovarian cancer and gynecologic malignancies (MITO) are promoting research activities in the field of gynecologic oncology on a national basis, even in the era of COVID-19. Methods: The SIGO and MITO group promoted a national survey aiming to evaluate the impact of COVID-19 on clinical activity of gynecologist oncologists and the implementation of containment measures of COVID-19 diffusion. Results: Overall, 604 participants completed the questionnaire with a response rate of 70%. The results of this survey suggest that gynecologic oncology units had set a proactive approach to COVID-19 outbreak. Triage methods were adopted in order to minimize the in-hospital diffusion of COVID-19. Although 73% of the participants stated that COVID-19 has not significantly modified their everyday practice, 21% declared a decrease in the use of laparoscopy in favor of open (19%) and vaginal (2%) surgery. Interestingly, about 5% of the participants stated that the use of laparoscopic surgery has increased during the COVID-19 outbreak. However, less than 50% of surgeons adopted specific protection against COVID-19. Additionally, responders suggested to delay cancer treatment (10–15%), and to perform less radical surgical procedures (20–25%) during COVID-19 pandemic. Conclusions: International cooperation is of paramount importance, as heavily affected nations can serve as an example to find out ways to safely preserve clinical activity during the COVID-19 outbreak